New Percepts via Mental Imagery? - Mast, Fred W.; Tartaglia, Elisa; Herzog, Michael (Frontiers in Psychology, 2012)
We are able to extract detailed information from mental images that we were not explicitly aware of during encoding. For example, we can discover a new figure when we rotate a previously seen image in our mind. However, such discoveries are not “really” new but just new “interpretations”. In two recent publications, we have shown that mental imagery can lead to perceptual learning (Tartaglia et al., 2009, 2012). Observers imagined the central line of a bisection stimulus for thousands of trials. This training enabled observers to perceive bisection offsets that were invisible before training. Hence, it seems that perceptual learning via mental imagery leads to new percepts. We will argue, however, that these new percepts can occur only within “known” models. In this sense, perceptual learning via mental imagery exceeds new discoveries in mental images. Still, the effects of mental imagery on perceptual learning are limited. Only perception can lead to really new perceptual experience.